BACTERIAL Cr (VI) REDUCTION AND ITS IMPACT IN BIOREMEDIATION - Pramono, Ali; Rosariastuti, MMA Retno; Ngadiman, N; Prijambada, Irfan D (Jurnal Ilmu Lingkungan, 2013)
ABSTRACTChromium is hazardous pollutant for ecosystem caused chromium especially inhexavalent form is very toxic, has high solubility and mobility, teratogenicity, mutagenicity andcarcinogenicity to living system related with its oxiding power. Remediation of soilcontaminated of heavy metals was important caused soil as medium for food producing.Conventional methods for heavy metals remediation consist of physical and chemical processbut these applications were costly and less effective. One of the remediation technologies is theusing living organisms such as microorganisms, because they have ability to reduce Cr(VI) intonon toxic form, Cr(III). The aims of this research were to evaluate the reduction activity ofrhizobacterial isolate and to identify the isolate which take a role in reducing chromiumabsorption by plant. The results showed that Isolate 39 was able to grow on LB mediumcontaining 200 ppm Cr(VI). Isolate 39 reduced Cr(VI) up to 15 ppm concentration level inminimal medium. Isolate 39 has ability to reduce Cr(VI) both at growing cells and resting cellsconditions up to 100% and 51% within 18 hours, respectively. Isolate 39 increased thephytostabilization ability of chromium by Zea mays at 30 days after seeding 3.8 timescompared than control. Based on physiological characteristics and partial sequencing of 16SrRNA gene, Isolate 39 was identified as Agrobacterium sp.Key words : Agrobacterium sp, hexavalent chromium, reduction, Zea mays